Mathematical modelling of "Reactor - Stabilization column" system in catalytic dewaxing of diesel oil cuts and atmospheric gasoil; Chemical Reactors (CHEMREACTOR-22) - Belinskaya N. S. Natalia Sergeevna; Popova N. V. Nataljya Vladimirovna; Frantsina E. V. Evgeniya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna (2016, 2016)
Title screen